Description of Adolescents' Mental Health During the Covid-19 Pandemic in Majalangu Village, Watukumpul Sub-District, Pemalang Regency - Lisa Dewi Diana Sari; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2022)
Background: The COVID-19 pandemic greatly affects mental health among adolescents. Adolescents are one of the most vulnerable groups to mental health due to a lack of activity and time to play with peers. They just stay at home and study online. Objective: This study aims to figure out the overview of mental health, which includes symptoms of depression, anxiety, somatic, and decreased energy in adolescents in Majalangu Village, Watukumpul Sub-district, Pemalang Regency. Method: This was a retrospective study with a sample of 88 respondents who were selected using the proportional random sampling technique. Results: The study using the SRQ-20 showed that 54 respondents (61.4%) were mentally healthy while 34 respondents (38.6%) were not. Conclusion: There were four symptoms in the overview of adolescent mental health: symptoms of depression, characterized by feelings of worthlessness (66.67%); symptoms of anxiety, characterized by feelings of tension, anxiety, and worry (64.81%); symptoms of somatic, characterized by headaches (57.41%); and symptoms of decreased energy, characterized by feeling easily tired (92.59%).